PROTOYPE MONITORING PRESENSI SISWA MENGGUNAKAN FINGER PRINT DENGAN KENDALI RASPBERRY PI - Mohammad Bhanu Setyawan; Adi Fajaryanto Cobantoro; Angga Prasetyo (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
One character that can be shaped in students at school is discipline. The exact time to enter school is one of the criteria for discipline that is applied in the Aliyah Negri 2 Ponorogo Madarasah. In order to improve information services to student guardians, MAN 2 Ponorogo changed the way manual attendance was made to students with fingerprint technology. But there are shortcomings in the use of fingerprint machines, the presence data on the machine is not real time in reporting student attendance to schools and student guardians. The solution is to integrate a fingerprint machine with Raspberry pi control. The Raspberry pi will automatically process the presence data inside the fingerprint machine so that it can be accessed via the web wherever the user is located and automatically sends the attendance report to the guardian using the telegram media. The design of this study uses the waterfall method in designing application prototypes and the results are tested using the blackbox method with a boundary value analysis technique. In subjective testing the system will be tested using a questionnaire about the ease of using the system to users.